CONDUCT RESEARCH STOCK MARKET BASED ON MODELS OF ARCH - Burtnyak, I.V.; Malitska , G. P. (The actual problems of regional economy development, 2016)
The purpose of this article is to study the dynamics of the volatility of some indicators of financial market of Ukraine using the methods ARCH modeling. As indicators of the financial market we take the most aggregated variables describing profitability or market price of the portfolio, but not individual assets constituting the portfolio. An indicator of the stock market index stands First Stock Trading System (PFTS). The conditional variance of financial indicators reflecting the level of systemic risk, measures the uncertainty associated with forecasting market dynamics. JEL: C 50